Traditional health care system of central Asia: an appraisal - Hassan, Rehana; Abdullah, Darakhshan (Journal of Social Review and Development, 2024)
Undeniably, a comprehensive health sector in Central Asia was developed by soviet regime, since Communists perceived healthy generation a backbone for attainment of economic growth and sustainable development of socialist society. However, introduction of biomedicine in the regions is attributed to the czarist regime who after conquest introduced public health system, though on a very small scale and primarily for use of military and administrative personnel. Prior to Russians, the region had its traditional health care system which of course was primitive but many western scholars have acknowledged the skills of traditional healers for treating many diseases successfully. The paper intends to provide a viewed picture of traditional health caring practices of the region which has been over shadowed or undermined by most of the modern scholars partly due to the overall intellectual stagnation of the region during early 19th century and partly due to introduction of advanced public health care system of Soviets known as Semashko model during late 19the century. Paper reveals that natives had enough confidence on traditional health care and they preferred their traditional system in comparison to Russian health care, yet the influx of Russian immigrants followed by pandemic, plague and epidemic rendered traditional health care system obsolete. Moreover, the restrictions imposed by Soviet regime on traditional practitioners further limited the scope of traditional health care system.